Peran Kecerdasan Interpersonal dalam Perspektif Islam pada Siswa Sekolah Dasar di Era Revolusi Industri 4.0 - Tasnim Lubis; Nashran Azizan; Maulana Arafat (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2019)
Education becomes a spear in developing the potency that exists in students both physically and spiritually.Besides increasing competence, interpersonal intelligence is an important thing to apply to the learning process. Learning is not always about values, but it can shape attitudes, so that later students can be intelligent, skilled and characterized citizens. Innovations that develop continuously that is begun from the industrial revolution 1.0 to 4.0, become challenges and opportunities for educators in developing the potentials of students in order to create competently, character and reliable graduates. The presence of the industrial revolution 4.0 which is known as the digital era is not only opens wide interactions but also disrupts various fields in human life. One of them is education. Therefore the role of interpersonal intelligence in schools is expected to be able to bridge the student’s attitudes to be in accordance with the Qur'an and the Constitution 195 and can be integrated in the era of the industrial revolution 4.0.